The Effect of Breakfast Education Using The Uno Block Game on The Level of Knowledge and Attitudes of Elementary School Children - Pakas, Sry Wandayani; Manjilala, Manjilala; Agustian Ipa; Adriyani Adam (Saintify Publish, 2025)
Breakfast is a source of energy needed to carry out activities at school. Based on consumption analysis data. Based on consumption data analysis of 35,000 school-aged children in Indonesia, it shows that almost half (44.6%) of children who eat breakfast only get less than (15%) energy intake. of the nutritional needs that should be met (15-30%) in a day. The aim of this research was to determine the effect of breakfast education using the Uno block game on the level of knowledge and attitudes of West Bangkala State 9 elementary school children. This type of research is quasi experimental with a one group pre-test and post-test design in West Bangkala 9th state elementary school. The research was carried out on January 10 2024. The sampling method used a total sampling technique with all 27 class V students and 33 class VI students. The variables in this research are knowledge and attitudes about breakfast, collected by filling out a questionnaire. Data analysis uses statistical tests, namely the Wilcoxon test. The results of the research revealed the level of knowledge of the sample before being given education (50.9%), the level of knowledge of the sample after being given education (100%). Attitudes before being given education (69.1%) and attitude levels after being given education (100%). The average knowledge score before education (53.45%) and after education (79.45%). The average attitude value before education (62.54) and after education (78.90%). Statistical analysis shows that there is a difference in knowledge before and after being given education (p=0.000) and statistical analysis shows that there is a difference in attitudes before and after being given education (p=0.000). It is recommended that for further research, further research can be carried out using Uno beam media in the target group, namely children and teenagers.